Increased energy expenditure, dietary fat wasting and resistance to diet-induced obesity in mice lacking renin - Takahashi, Nobuyuki (2007)
An overactive renin angiotensin system is associated with obesity and the metabolic syndrome. However, mechanisms behind it are unclear. Cleaving angiotensinogen to angiotensin I by renin is a rate-limiting step of angiotensin II production, but renin is suggested to have angiotensin-independent effects. We generated mice lacking renin (Ren1c) using embryonic stem cells from C57BL/6 mouse, a strain prone to diet-induced obesity. Ren1c-/- mice are lean, insulin sensitive, and resistant to diet-induced obesity without changes in food intake and physical activity. The lean phenotype is likely due to a higher metabolic rate, and gastrointestinal loss of dietary fat. Most of the metabolic changes in Ren1c-/- mice were reversed by angiotensin II administration. These results support a role for angiotensin II in the pathogenesis of diet-induced obesity and insulin resistance.